Dicarbocyanine dye-based organic photodiodes - Md Sabri, Amirul Ashraf; Natashah, Fadlan Arif; Hisamuddin, Syaza Nafisah; Roslan, Nur Adilah; Bawazeer, Tahani M.; Alsoufi, Mohammad S.; Supangat, Azzuliani (MDPI, 2022)
We report on the utilization of 1′-1′-diethyl-4,4′-dicarbocyanine iodide (DDCI-4) as a photoactive material for organic photodiodes (OPDs). A device was fabricated using a ternary blended ratio in the conventional stack order of ITO/PEDOT:PSS/P3HT:DDCI-4:OXCBA/Al to improve stability and enhance light absorption. An investigation was carried out into the optical and morphological characteristics of the device along with its electrical performance using different concentrations of DDCI-4 in a blended ratio of P3HT:DDCI-4:OXCBA in the photoactive layer. The mechanism of the OPD device and its performance with a gradual increase in DDCI-4 concentration is explained throughout this work, in which the increase in DDCI-4 concentration caused the dislocation defect and a decrease in charge carriers. The appropriate concentration of DDCl-4 resulted in improved light broadening, especially in near-infrared (NIR) regions.